Analisis Laju Korosi Pada Logam Melalui Proses Dipcoating Larutan Elektrolit - Miranda Miranda; Rahmawati Rahmawati (Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to determine how to test the rate of metal corrosion using dip-coating electrolyte solutions. The electrolyte solutions used are vinegar, lime juice, saltwater, and rainwater—this research conducted by the method of losing weight by dipping the electrolyte solution. The sample immersed for 27 days. The calculation results obtained and samples without coating have a high corrosion rate, so they destroyed quickly. The higher the value of the corrosion rate, the more easily destroyed it will be, and the sample will easily weather/damaged. Likewise, on the contrary, the lower the corrosion rate, the less corrosion that occurs, and the better the sample is protected from rust.